2012
DOI: 10.1371/journal.pone.0046988
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Complete Integration of HIV and TB Services on Time to Initiation of Antiretroviral Therapy: A Before-After Study

Abstract: BackgroundStudies have shown that early ART initiation in TB/HIV co-infected patients lowers mortality. One way to implement earlier ART commencement could be through integration of TB and HIV services, a more efficient model of care than separate, vertical programs. We present a model of full TB/HIV integration and estimate its effect on time to initiation of ART.Methodology/Principal FindingsWe retrospectively reviewed TB registers and clinical notes of 209 TB/HIV co-infected adults with a CD4 count <250 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 38 publications
(23 reference statements)
2
52
0
Order By: Relevance
“…An increasing number of studies from routine services in resource-limited settings have reported increased and expedited ART uptake, [26][27][28][29][30][31][32][33][34][35] especially after the introduction of a package of interventions aiming at achieving integration of tuberculosis and HIV care. These studies generally precede the 2010 WHO ART guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies from routine services in resource-limited settings have reported increased and expedited ART uptake, [26][27][28][29][30][31][32][33][34][35] especially after the introduction of a package of interventions aiming at achieving integration of tuberculosis and HIV care. These studies generally precede the 2010 WHO ART guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Median ART delays of 7 and 11 weeks in Uganda and South Africa, respectively, were still observed after integration in recent studies. 29,32 An interesting aspect of our study is that early ART initiation was implemented as a single intervention, without major concurrent changes in the tuberculosis/ HIV service delivery model. This makes it possible to better quantify the effect of the revised guidelines and to demonstrate their impact when coordination of tuberculosis/HIV activities is fairly well organized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Capetown, South Africa assesses the impact of adding ART initiation to a TB clinic that already offered HIV testing, CD4 counts, co-trimoxazole prophylaxis and FP, but previously referred treatment-eligible patients to a separate ART clinic for treatment (Kerschberger et al 2012). The study finds that adding ART initiation to the range of services improved the probability of initiation (1.6 adjusted HR, 95% CI: 1.11 to 2.29) and may have also improved the time between HIV testing and ART initiation, which decreased from 147 days (95% CI: 85 to 188) to 75 days (95% CI: 52 to 119).…”
Section: Tuberculosismentioning
confidence: 99%
“…This heightens the operational importance of integrated TB/HIV services. Integrated care was shown to increase ART initiation by 60 % among co-infected patients, reducing time to initiation by more than 2 months (72 days) on average [10]. Randomized trials have shown that early ART initiation (2 weeks after the onset of anti-TB treatment) vs later ART initiation (8 weeks after) reduces mortality among advanced immunodeficient (B50 CD4 cells/mm 3 ) HIVpositive patients who are smear positive for acid-fast bacilli [5,6,9].…”
Section: Introductionmentioning
confidence: 99%